La Demanda de Dinero por Motivo Transaccion en Chile. - Adam, C (2000)
This paper examines the transactions demand for money in Chile over the period from 1986 to 2000. Using systems cointegration methods suggested by Johansen (1995), we find that although macroeconomic data for Chile exhibit strong trend-stationarity during this period it is possible to recover relatively robust single-equation specifications for the transactions demand for money. Error-correction models in which money demand is conditioned on real wealth, the level of economic activity, and the nominal Central Bank policy rate provide robust basis for inference. Controlling for a shift in velocity at the end of 1998 the models exhibit a high-degree of out-of-sample predictive power over the period from 1998 to mid 2000.